Strategic policy-making for natural resources management in Iraq and control the related constraints to achieve sustainable development between reality and ambition - Murad, Abbas Gulmurad Beg (Journal of Petroleum Research and Studies, 2020)
Natural resources can provide transformational opportunities to support development but ultimately are depleted resources. How can Iraq optimize these limited resources while managing a complex sector while minimizing affect at the local level In the long run, natural resources can transform Countries in the area of ​​development or other forms of income in the case of good governance. Wealth of natural resources can also have a significant affect on the country's sustainable development efforts, as well as many other direct and indirect benefits of the Iraqi economy. But these benefits do not happen spontaneously Indeed, in many cases wealth from natural resources does not turn into long-term sustainable development because of the many real challenges associated with resource-based development. Many of these deposits are located in places with governance-related constraints and significant development-related challenges. There are also economic challenges in managing the volatile revenues of natural resources and technical complexities associated with the management of these large-scale projects. There are real risks of environmental and social imbalances and impacts. The interests have different and different interests. In many cases, these agreements are surrounded by secrecy, in addition to other reasons. In this paper we highlight the challenges faced by rich countries in natural resources in trying to contain Resources to sustainable development and management of investments in the extractive industries in a sustainable manner and to clarify the complex and overlapping governance of natural resources aspects, as well as in some of the strategies that help some countries, including Iraq, to ​​achieve success and the optimal use of these resources to achieve long-term development.